Influence of medium and gelling agents concentration on in vitro rooting of Polygonum tinctorium - Choi, Minsol; Kim, Haeng-Hoon; Seo, Hyewon; Sathasivam, Ramaraj; Kim, Jae Kwang; Park, Sang Un (Journal of Phytology, 2024)
Polygonum tinctorium has long been employed in the medical and dye industries in many nations, particularly in Korea and Japan, for traditional fabric staining as a source of blue color. The plant tissue culture method has proven to be a rapid and sustainable approach for the regeneration of various plant species, particularly those with medicinal or ornamental value. In this study, we explored the in vitro root regeneration and growth of P. tinctorium in response to different growth media and gelling agents. Among the tested media, Schenk and Hildebrandt medium (SH medium) demonstrated superior performance, resulting in the highest number and length of roots per explant. SH media produced about 53 and 18% higher root per explant and a 40% and 14% increase in root length compared to B5 and MS media, respectively. Half strength of SH medium proved to be the optimal condition for both root number (7.46 roots per explant) and root length (3.81 mm). Among the gelling agents, 2 g/L of Gelrite medium was most effective in promoting the highest and tallest roots. These findings have the potential to enhance rooting abilities in various crops, particularly in the case of medicinal and ornamental plants, and may offer valuable insights for future industrial-scale root production of P. tinctorium.